1997
DOI: 10.4049/jimmunol.159.5.2484
|View full text |Cite
|
Sign up to set email alerts
|

Repeated elicitation of contact hypersensitivity induces a shift in cutaneous cytokine milieu from a T helper cell type 1 to a T helper cell type 2 profile.

Abstract: We previously demonstrated that repeated application of 2,4,6-trinitro-1-chlorobenzene resulted in a site-restricted shift in the time course of Ag-specific hypersensitivity responses from a typical delayed-type to an early-type response. Here we demonstrated that the cutaneous microenvironment at the time of Ag presentation to T cells in the elicitation, but not the induction, phase of contact hypersensitivity is responsible for the shift. To investigate the differences in the cutaneous cytokine milieu betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Various animal models have been established to study AD pathogenesis, and one such widely used model is the mouse model of chronic allergic contact dermatitis induced by repeated hapten application. Kitagaki et al (1995Kitagaki et al ( , 1997 reported that in this model, the skin lesions show findings similar to the reported clinical manifestations, such as edema; epidermal hyperplasia; CD4 + cell, granulocyte, and mast cell infiltration; and dominant T helper 2 cell cytokine expression.…”
Section: Discussionsupporting
confidence: 76%
“…Various animal models have been established to study AD pathogenesis, and one such widely used model is the mouse model of chronic allergic contact dermatitis induced by repeated hapten application. Kitagaki et al (1995Kitagaki et al ( , 1997 reported that in this model, the skin lesions show findings similar to the reported clinical manifestations, such as edema; epidermal hyperplasia; CD4 + cell, granulocyte, and mast cell infiltration; and dominant T helper 2 cell cytokine expression.…”
Section: Discussionsupporting
confidence: 76%
“…Our literature search shows that this classification is difficult for hlAD murine skin. Chen et al [55] reports that TH2 cytokines are more prominent in disease stages while Kitagaki et al [56] shows that a prolonged antigen treatment leads to a shift from a TH1 to a TH2 cytokine response and a study on Stat6VT mice reveals a simultaneous increase in IL-4 and IFN-γ mRNA expression from the acute to chronic phase [57]. Since data are limited, an explicit assignment to an acute or chronic stage of the DNCB-treated skin lesions, as it is described for human AD, is not yet possible in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Elevations of proinflammatory cytokines have also been noted in cardiovascular disease and act by increasing insulin resistance or oxidizing low density lipoproteins, thus denoting a common disease etiopathogenesis 6,23 . In addition, it has been suggested that chronic ACD may shift the cytokine balance from a T helper (Th)1 to a T H 2-mediated process; thus, chronic ACD could potentially be associated with similar comorbidities to other diagnoses that share overactivation of the T H 2 axis, such as AD 24 . Furthermore, gene expression and cellular studies have demonstrated that ACD immunopathogenesis is mediated by T H 1, T H 17, and T H 2 pathways in an allergen-dependent manner; the T H 17 pathway has been correspondingly implicated in the pathogenesis of cardiovascular diseases in both in vivo and clinical studies 22,25,26 …”
Section: Discussionmentioning
confidence: 99%
“…6,23 In addition, it has been suggested that chronic ACD may shift the cytokine balance from a T helper (Th)1 to a T H 2-mediated process; thus, chronic ACD could potentially be associated with similar comorbidities to other diagnoses that share overactivation of the T H 2 axis, such as AD. 24 Furthermore, gene expression and cellular studies have demonstrated that ACD immunopathogenesis is mediated by T H 1, T H 17, and T H 2 pathways in an allergen-dependent manner; the T H 17 pathway has been correspondingly implicated in the pathogenesis of cardiovascular diseases in both in vivo and clinical studies. 22,25,26 ACD was significantly associated with obesity, hypertension, and hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%